Constitutional Limits of Emergency Powers: Judicial Review and Democratic Resilience in Contemporary Constitutional States - Josef Okemba; Muhammad Ridho Rahman; Ihsan Ihsan (International Journal of Law and Political Authority, 2026)
The expansion of emergency powers in contemporary constitutional states has generated profound tensions between the necessity of rapid executive action and the preservation of constitutional limits, particularly in contexts where extraordinary measures risk normalizing deviations from democratic principles and weakening institutional checks and balances. This study addresses the unresolved problem of how constitutional systems can effectively constrain emergency powers while maintaining democratic resilience, with a specific focus on the role of judicial review as a mechanism of constitutional control. Employing a normative juridical method grounded in doctrinal and comparative legal analysis, this research examines constitutional provisions, emergency law statutes, and constitutional court decisions derived from constitutional court databases, supported by interpretive approaches including systematic, teleological, and comparative methods. The findings reveal that constitutional limits are operationalized through judicial review practices that conditionally validate emergency measures while imposing substantive and procedural constraints, thereby preventing the entrenchment of exceptional governance. The analysis further demonstrates that the effectiveness of these limits depends on institutional integrity, interpretive coherence, and socio-legal factors such as constitutional culture and public trust, which collectively shape the capacity of constitutional systems to withstand crisis without eroding democratic norms. This study contributes to the theoretical development of constitutional resilience by integrating normative, empirical, and socio-legal perspectives, while also offering methodological insights through the combined use of doctrinal analysis and judicial data.